Stakeholder Identification and Salience After 20 Years: Progress, Problems, and Prospects. Issue 1 (January 2021) - Wood, Donna J.; Mitchell, Ronald K.; Agle, Bradley R.; Bryan, Logan M.
To contribute to the continuing challenge of explaining how managers identify stakeholders and assess their salience, in this article, we chronicle the history, assess the impact, and evaluate the possibilities opened by Mitchell, Agle, and Wood (MAW-1997). We do so through two types of qualitative analysis, and also through utilizing a quantitative network analysis tool. The first qualitative analysis categorizes the major contributions of the most influential papers succeeding MAW-1997; the second identifies and compares the relevant issues with MAW-1997 at the time of initial publication and today. We apply main path analysis, a quantitative tool, to map how this scholarly domain has evolved. These three analyses robustly depict the impact of MAW-1997 and the ensuing scholarly conversation, and they enable us to illustrate the current state and trajectory of stakeholder identification and salience scholarship. We close by discussing pressing topics related to the broader body of stakeholder theory literature.